2022
DOI: 10.1161/circulationaha.122.060666
|View full text |Cite|
|
Sign up to set email alerts
|

Early Versus Delayed Non–Vitamin K Antagonist Oral Anticoagulant Therapy After Acute Ischemic Stroke in Atrial Fibrillation (TIMING): A Registry-Based Randomized Controlled Noninferiority Study

Abstract: Background: There are no evidence-based recommendations on the optimal time point to initiate non–vitamin K antagonist oral anticoagulants (NOACs) after acute ischemic stroke in patients with atrial fibrillation. We aimed to investigate the efficacy and safety of early versus delayed initiation of NOAC in these patients. Methods: TIMING (Timing of Oral Anticoagulant Therapy in Acute Ischemic Stroke With Atrial Fibrillation) was a registry-based, randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 36 publications
1
58
0
1
Order By: Relevance
“…In the TIMING trial, 33 patients with AF-related stroke randomized within 72 h to early (⩽4 days) DOAC was noninferior to delayed (5–10 days) DOAC, with 1.79% absolute risk difference of composite of recurrent ischemic stroke, symptomatic intracerebral hemorrhage, or all-cause mortality at 90 days. Symptomatic HT rates in the TIMING trial and our study were both zero.…”
Section: Discussionmentioning
confidence: 99%
“…In the TIMING trial, 33 patients with AF-related stroke randomized within 72 h to early (⩽4 days) DOAC was noninferior to delayed (5–10 days) DOAC, with 1.79% absolute risk difference of composite of recurrent ischemic stroke, symptomatic intracerebral hemorrhage, or all-cause mortality at 90 days. Symptomatic HT rates in the TIMING trial and our study were both zero.…”
Section: Discussionmentioning
confidence: 99%
“…22 The recently published Timing of Oral Anticoagulant Therapy in Acute Ischemic Stroke With Atrial Fibrillation ( TIMING ) study was the first RCT on this topic and showed that early initiation of anticoagulation was noninferior to delayed initiation concerning a composite endpoint of ischemic stroke, death, and ICH. 2 The results of other currently ongoing RCTs, that is, ELAN, 5 OPTIMAS, 4 and START, 3 are eagerly awaited. Real-world evidence reflecting the initiation or resumption of anticoagulants in daily practice is crucial as a complement to data derived from RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Delaying the initiation of anticoagulation, however, may enhance the risk of recurrent ischemic events. 1 With one exception, 2 results from randomized controlled trials (RCTs) on the timing of anticoagulation [3][4][5] are not yet available and guidelines are currently based on expert opinion. [6][7][8] Surveys among stroke practitioners on timing of anticoagulation following AIS or TIA have shown no consensus in decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical benefits of early anticoagulation are widely recognized and safe, 26.9% did not achieve appropriate control objectives [ 18 , 38 , 39 , 40 , 41 , 42 , 43 ]. This fact increases the impact of the unknown AF ( Table S1 ).…”
Section: Discussionmentioning
confidence: 99%